2022
DOI: 10.3389/fmed.2022.940454
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and probiotic-based vaccines: A novel approach for improving vaccine efficacy

Abstract: Vaccination is defined as the stimulation and development of the adaptive immune system by administering specific antigens. Vaccines' efficacy, in inducing immunity, varies in different societies due to economic, social, and biological conditions. One of the influential biological factors is gut microbiota. Cross-talks between gut bacteria and the host immune system are initiated at birth during microbial colonization and directly control the immune responses and protection against pathogen colonization. Imbal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 146 publications
(154 reference statements)
1
8
0
Order By: Relevance
“…The effectiveness of vaccines depends on different factors, one of the most influential being the intestinal microbiota ( 8 ). Interactions between gut bacteria and the immune system begin immediately after birth, directly influencing the immune response and, thus, protecting against pathogens ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of vaccines depends on different factors, one of the most influential being the intestinal microbiota ( 8 ). Interactions between gut bacteria and the immune system begin immediately after birth, directly influencing the immune response and, thus, protecting against pathogens ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…When there are changes in the composition of the gut microbiota, it can lead to several immune disorders, thereby impairing the proper response to immunization ( 31 ). Metabolic diseases such as diabetes can alter the gut microbiome and disrupt gut bacterial equilibrium ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As SARS-CoV-2 infections continue to rise even among vaccinated individuals [ 28 , 29 ], there is an urgent call for an alternative vaccine platform that is less expensive, readily scalable, as well as easier to store and administer, as this would overcome the major limitations of the current COVID-19 vaccines [ 30 ]. Other authors have previously suggested [ 31 , 32 ] the use of probiotic strains as delivery systems for viral or bacterial antigens with promising results, including SARS-CoV-2 [ 13 , 33 ]. In this study, we proposed a new immunization approach using plasmid transfection by inducing the widely used apathogenic EcN strain to express and expose SARS-CoV-2 SP on the bacterial surface.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota’s interaction with the host promotes the intestinal epithelial barrier, improves immune homeostasis, protects from pathogen colonization, and inhibits deleterious inflammatory reactions. Therefore, the gut microbiota’s composition can affect the normal mucosal immune system, while the imbalances in the gut microbiota’s composition, termed dysbiosis, can trigger several immune disorders through the activity of the adaptive immune system [ 18 ].…”
Section: Introductionmentioning
confidence: 99%